The LOWER URINARY TRACT SYMPTOMS IN ANURIA AND NON-ANURIA PATIENTS AFTER RENAL TRANSPLANTATION: A COMPARATIVE STUDY - Rahmita, Maulidina Medika; Harrina Erlianti Rahardjo; Arry Rodjani; Nur Rasyid (Indonesian Journal of Urology, 2021)
Objective: The purpose of this study is to examine the difference of lower urinary tract (LUT) symptoms in anuric and non-anuric individuals after renal transplantation (RT). Material & Methods: LUT function and symptoms were assessed in subjects who had undergone RT at Cipto Mangunkusumo General Hospital, Jakarta, from November 2016 to June 2017. Subjects were divided into anuric and non-anuric groups. We excluded patients with surgical complications that could not undergo uroflowmetry. Results: Thirty-two (21 male, 11 female) subjects were recruited in this study. The anuric subjects were younger than the non-anuric ones (47 ± 12.82 vs. 51.31 ± 16.33, p < 0.001) There were no significant differences in the International Prostate Symptoms Score (IPSS) (6.5 ± 3.67 vs. 6.25 ± 2.95, p = 0.567), Overactive Bladder Symptoms Score (OABSS) (4.06 ± 2.01 vs 4.12 ± 2.39, p = 1.000), maximum urinary flow rate (Qmax) (20.32 ± 9.04 vs. 22.32 ± 10.31, p = 0.956), post-void residual (PVR) (41.12 ± 37.63 vs. 47.62 ± 38.63, p = 0.361) and voided volume (227.88 ± 112.30 vs 251.06 ± 126.75, p = 0.588) between anuric and non-anuric subjects, respectively. IPSS-voiding symptom, IPSS-storage symptom, and OAB symptom did not differ significantly between both groups (p > 0.05). Thirteen (13/16) and seven (7/16) subjects of the anuric and non-anuric groups were both pleased with their quality of life, respectively. Conclusion: LUT symptoms do not differ between anuric and non-anuric patients.